Lability and the rigidification of word order: evidence from Early Middle English - García García Luisa (Linguistics)
This article analyzes quantitatively the effect of five linguistic features on the position of the object in Early Middle English. Four of them have long been explored in the literature: object type, object length, clause type and type of verbal cluster (±auxiliary). The fifth feature, lability, has so far been given less attention. Lability is the possibility that a given verb alternates between an unaccusative and transitive frame without morphological coding. This makes lability an instance of morphological syncretism. This study tests the hypothesis that, for disambiguation purposes, labile transitive verbs show a more consistent word order (VO in this case) than non-labile transitives. If confirmed, the hypothesis would point to a non-trivial connection between the increase of labile verbs and the move towards a fixed word order in Early Middle English. Such a connection has gone unnoticed in the existing literature, which, as far as the influence of morphological syncretism on word order is concerned, has focused almost exclusively on the effect of the loss of case marking. A total of 961 transitive clauses with labile and non-labile verbs were tagged for the above-mentioned five variables. Their effect on the choice between VO and OV is measured using statistical analysis. The conclusion is that verb lability is a significant predictor of VO in the period under scrutiny, with labile verbs thus spearheading the shift towards a stable word order pattern (VO) in English. The correlation between verb lability and word order rigidification demonstrated for Early Middle English in this article may be relevant for studies on word order from multiple perspectives: language-specific, typological, synchronic and diachronic.